Pelatihan Budidaya Dan Pemasaran Sayur Kangkung Dan Bayam Untuk Meningkatkan Harga Jual Di Kelurahan Panorama Kecamatan Singaran Pati Kota Bengkulu - Jatmiko, Wendi; Sumartono, Eko; Saputra, Roy; Nugroho, Arjun Satrio; Illahi, Abdul (Jurnal INDONESIA RAYA (Pengabdian pada Masyarakat Bidang Sosial, Humaniora, Kesehatan, Ekonomi dan Umum), 2024)
Cultivation is the action of managing biological resources to extract the results or it can also be interpreted as an effort to maintain plants or livestock starting from preparing seeds or seedlings to harvest the results. Kale and spinach are vegetables that are popular with the public and the prices are quite cheap. But currently, marketing of kale and spinach vegetables is experiencing problems in increasing sales in a sustainable manner because product marketing relies on traditional marketing methods, such as direct sales. By relying on traditional marketing methods with business management, this has an impact on sales operational costs which are quite high and capital turnover becomes slow, resulting in slow production. Therefore, our team of lecturers and students from Unived Agricultural Agribusiness provides simple cultivation and marketing training, especially applying the 4p theory which will improve the quality of cultivation and marketing of kale and spinach vegetables. The method used is a qualitative method with a descriptive approach. In compiling this community service report the author used observational data collection techniques, library study methods and documentation methods. The results of this service are very helpful for KWT Merapi Zero business owners in cultivation and marketing.